Criminal Law Policy in Efforts to Combat Artificial Intelligence (AI) in Cyber Crime - Dharmayanti, Yuliana Putri; Soponyono, Eko (UNISSULA Semarang, 2025)
The development of Artificial Intelligence (AI) technology has had a major impact on various areas of life, including in the criminal law aspect. AI is not only used for positive purposes, but also opens up opportunities for new cybercrimes such as deepfakes, automated phishing, and digital identity theft. These crimes pose new challenges in law enforcement, especially regarding criminal liability and the lack of legal regulations that specifically regulate AI-based crimes. This study aims to analyze criminal law policies in dealing with AI-based cybercrime, both in the current positive law and the prospects for its regulation in the future. This study uses a normative legal method with a descriptive-analytical approach. Data were collected through a literature study of laws and regulations such as the Criminal Code, the ITE Law, and relevant literature. The results of the study indicate that existing regulations have not explicitly regulated the use and misuse of AI in cybercrime. The applicable legal provisions are still general and have not been able to accommodate the complexity of AI-based crimes. This indicates a legal vacuum that must be filled immediately through the renewal of criminal law policies that are more adaptive and progressive to the development of information technology. Based on the results of the analysis, a reformulation of criminal law policies is needed that can answer the challenges of AI-based cybercrime through the approach of the theory of the rule of law, the theory of criminal responsibility, and the theory of criminal policy. This research provides a theoretical contribution to the development of criminal law in the digital era, as well as being a practical reference for policy makers in formulating relevant and effective regulations. Thus, it is hoped that the Indonesian legal system can respond to technological developments by creating regulations that are fair, clear, and able to protect the public from increasingly complex cybercrimes.